2005
DOI: 10.1055/s-2004-821326
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variation in the Reduction of Heart Rate and Performance at Lactate Thresholds in Acute Normobaric Hypoxia

Abstract: Heart rate monitoring and lactate measurements are used to control exercise intensity during training at moderate altitude although there is some uncertainty about hypoxia-induced changes in these parameters at equivalent submaximal exercise intensities compared to normoxia. To study the influence of acute normobaric hypoxia (FiO2 0.15) on heart rate and performance at the individual anaerobic lactate threshold (IAT), at the 4 mmol x l(-1) threshold (AT) and at an intensity requiring 80 % of VO2max measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 28 publications
2
28
1
Order By: Relevance
“…Although previous studies (Levine et al, 1992;Desplanches et al, 1993;Beidleman et al, 2003) showed that training in hypoxia improves aerobic performance in hypoxia, we attribute this difference between HG and NG to the fact that HG might have been somewhat better trained prior to the study. HG reached almost the same values for P max and Vo 2 max as NG, despite being tested at an Fio 2 ¼ 0.15, which is expected to decrease both P max and Vo 2 max by about 15% to 20% (Friedmann et al, 2005).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although previous studies (Levine et al, 1992;Desplanches et al, 1993;Beidleman et al, 2003) showed that training in hypoxia improves aerobic performance in hypoxia, we attribute this difference between HG and NG to the fact that HG might have been somewhat better trained prior to the study. HG reached almost the same values for P max and Vo 2 max as NG, despite being tested at an Fio 2 ¼ 0.15, which is expected to decrease both P max and Vo 2 max by about 15% to 20% (Friedmann et al, 2005).…”
Section: Discussionmentioning
confidence: 76%
“…To be able to train subjects at the same relative workload in both groups, ergometry was performed at an Fio 2 ¼ 0.15 (ambient Po 2 equivalent to 3000 m) in the HG and in normal room air (altitude <100 m) in the NG. Since performance decreases at Fio 2 ¼ 0.15 (Friedmann et al, 2005) by 15% to 20%, ergometry was started at 40 W, with an increment of 40 W every 3 min in HG; starting load and increments were 50 W in NG. The adjustment of workloads resulted in similar test durations in both groups and helped to conceal the test condition from subjects with prior experience in such testing.…”
Section: Preexaminationmentioning
confidence: 99%
“…The physiological response of human body to hypoxia is variabial (Angermann et al 2006;Friedmann et al 2005). In past studies, however, all the subjects were given the same hypoxic gas without concerning the individual variability.…”
Section: Discussionmentioning
confidence: 99%
“…Although this phenomenon is well described, a wide interindividual variability in the magnitude of reduction of V O 2max at a given level of hypoxia has been reported by several laboratories (8,14,28,31,37). Of note is the observation that the hypoxia-induced reduction in V O 2max is greater in endurance athletes than in sedentary subjects (28).…”
mentioning
confidence: 96%